2020
DOI: 10.7717/peerj.10027
|View full text |Cite
|
Sign up to set email alerts
|

Genetic identification and hybridization in the seagrass genusHalophila(Hydrocharitaceae) in Sri Lankan waters

Abstract: Seagrasses, as marine angiosperms, play important roles in coastal ecosystems. With increasing anthropogenic impacts, they are facing dramatic declines on a global scale. Halophila is well-known as a complex taxonomic challenge mainly due to high morphological plasticity. By using only a morphological approach, the genus could be over-split or similar species could be erroneously lumped, thus masking its true biodiversity. In the present study, we incorporated genetic identification with morphological examinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…ramamurthiana in India there were no nucleotide differences found (Nguyen et al 2013). A recent study on the genus Halophila in Sri Lanka using ITS sequences showed a clade of Halophila ovalis complex which consisted of H. ovata, H. minor, H. ovalis, H. hawaiiana, and H. johnsonii (Liu et al 2020).…”
Section: Halodule Pinifoliamentioning
confidence: 87%
See 1 more Smart Citation
“…ramamurthiana in India there were no nucleotide differences found (Nguyen et al 2013). A recent study on the genus Halophila in Sri Lanka using ITS sequences showed a clade of Halophila ovalis complex which consisted of H. ovata, H. minor, H. ovalis, H. hawaiiana, and H. johnsonii (Liu et al 2020).…”
Section: Halodule Pinifoliamentioning
confidence: 87%
“…The rbcL region has been used to differentiate four seagrass species from Thailand (Osathanunkul et al 2015), identify Halophila spp. from Sri Lanka (Liu et al 2020), and identify other flowering plants such as Sonchus arvensis (Wahyuni et al 2019) and genus Piper (Naim and Mahboob 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, H. x tanabensis as a hybrid between H. nipponica and H. major was described [ 56 ]. More recently, a hybrid between H. ovalis and H. major has been demonstrated molecularly from Sri Lanka [ 75 ]. However, using new sequencing methods recommended by Yu et al [ 76 ] may resolve these conspecific species’ complexity and assist in future seagrass taxonomical research.…”
Section: Discussionmentioning
confidence: 99%
“…It is anticipated that some of the described Halophila species in this review may become synonyms after more studies are conducted in the future. On the other hand, there are potentially more new species in the Halophila yet to be described [ 75 , 83 ]. It has been suggested that the new species should be accepted if it is supported by genetic data [ 84 ].…”
Section: Discussionmentioning
confidence: 99%
“…The high morphological plasticity of species and the presence of locally adapted morphotypes could lead to erroneous species identification. This could favor in turn, the hybridization with native species, the breakdown of locally adapted ecotypes, and the establishment of hybrids (i.e., genetic swamping), potentially compromising the entire ecosystem functioning [98]. In this case, species identification should also be performed at a genetic level to overcome taxonomic ambiguity.…”
Section: Speciesmentioning
confidence: 99%